Effect of Theileria lestoquardi infection on some reproductive performance of experimentally infected Desert sheep in the Sudan - AdbAlla, Elmansoury, Y. H.; Elsaddig, Aisha, A.; H.S., Abdalla; Elbasheir, Husna, M.; Babikir, Amna, E.; Adam, Azza, A.; Abd Elmageed, Tahani, O.; Ali, Babeker, E. (Journal of Veterinary Medicine and Animal Production, 2021)
This study was aimed to investigate the effect of Theileria lestoquardi on the reproductive performance of Sudanese desert ewes. Thirty ewes were divided into three groups (A, B and C) of 10 each subjected to estrous synchronization and hand mating. Group A was infected before mating, group B was infected 2-3 months after conception and group C remained as uninfected control. Conception rate was found to be 11.1% in the first mating, and increased to 33.3% and 44.4% in the second and third mating for group A, GC reached 90%. In GB, three ewes aborted 20 days post infection. In GA the gestation period was two weeks shorter, body weight of the newly born lambs was reduced 30% and the mortality rate was 50%. All infected group revealed a delay in the first progesterone rise after delivery. Generally the infection of Theileria lestoquardi was highly affects the reproductive performance.